Analysis of Public Attitudes Regarding the Use of JKN Mobile - Siregar, Oktavia Sukmayati; Ismah, Zata; Hasibuan, Rapotan (Newinera Publisher, 2024)
The JKN mobile application aims to reduce queues at BPJS Kesehatan Branch Offices by providing the best service to the community. This research aims to improve JKN Mobile information system services in order to provide better services to the community. The study was conducted using a crossectional approach and quantitative descriptive method at the Batang Kuis Health Center in February 2024, with a population and sample using JKN Mobile of 70 patients with a total sample technique. The research instrument was a questionnaire with 10 questions using a Likert scale of 1-4. Currently, as many as 48% of the total population of Deli Serdang have become JKN participants. However, there are still many people who have not used JKN Mobile, except for patients who need referrals to hospitals. A survey shows that most of the 70 respondents who use JKN Mobile need a further understanding of the usefulness of the application. Based on the findings that the JKN Mobile application does not help consult doctors because this is rarely used by the public which causes them not to understand its use. In addition, education is also needed, especially for female respondents who still do not understand the use of the JKN Mobile application. One of the problems that is often complained by the community is the difficulty in the login process which causes forgetting usernames, passwords, and errors.